Sacred Words, Defiant Voices: Feminist Consciousness and Women’s Empowerment in Punjabi Sufi Verse - Ms. Rabia Ikram; Ms. Satwant Kour; Ms. Maria Khalid, (Dialogue Social Science Review (DSSR), 2025)
This research examines the convergence of feminist consciousness, religious agency, and poetic voice within the Punjabi Sufi poetry tradition, with a special focus on Bulleh Shah, Waris Shah, and Mian Muhammad Bakhsh. By means of a qualitative secondary data analysis of Sufi poetry, literary criticism, and feminist theological structures, the study examines how Punjabi Sufi literature presents subversive constructions of womanhood, resists patriarchal norms, and retrieves feminine voice in religious discourse. The research finds that Sufi poetry not only represents a space of mystical contemplation but also an subtle yet deep space of women's resistance, empowerment, and cultural continuity. Figures like Heer and Ranjha's beloved in Waris Shah’s Heer are read anew with a feminist approach, placing emphasis on their spiritual resilience, independence, and metaphorical resistance against oppressive social structures. By placing this question within the framework of spiritual feminism, the research adds to a richer comprehension of how mystic poetry serves as a vehicle for gendered agency, reconceptualizing the sacred as an arena of feminist possibility within South Asian literary and cultural contexts. Keywords: Punjabi Sufi Poetry, Feminism, Feminist Spirituality, Women’s Empowerment, Gender and Mysticism, South Asian Literature